Extractive Industries Transparency Initiative : Combating the Resource Curse in Fragile and Conflict-Affected Countries - Caspary, Georg (World Bank, Washington, DC, 2012)
Access to extractive industry resources, and to the revenues springing from them, is at the root of many conflicts. Recent examples include the several wars fought, in part, over access to oil in the Middle East and wars fueled by 'blood diamonds' in West Africa. The Extractive Industries Transparency Initiative (EITI), launched in 2002 and endorsed by the World Bank in 2003, has provided tangible governance improvements in resource-rich conflict-affected countries. It works with multiple stakeholders, a coalition of governments, companies, investors, international organizations, and civil society organizations (CSOs), to manage a process of publication and verification of company payments and government revenues from oil, gas, and mining. This smart lesson shares our experience implementing EITI in five prominent conflict countries and provides recommendations and lessons that may inform implementers of other World Bank programs in Fragile and conflict-affected countries.